Case Report: Retroperitoneal Sarcoma in Six Operations: Our Experience in Operative Management of Blood Vessels - Guo, Jinhui; Qiu, Fabo; Zhao, Jie; Lu, Qiliang; Fu, Wen; Xu, Qiuran; Huang, Dongsheng (Frontiers in Oncology, 2022)
Retroperitoneal liposarcoma is a malignant tumor that originates in soft tissues. Compared with other types of tumors, its biggest feature is a significant local recurrence rate [1-3]. Low-grade liposarcoma may not change for a long time in the patient's body, but once the sarcoma has poorly differentiated components, the sarcoma will progress rapidly and the waist circumference will also increase. The diameter of the tumor was about 26 cm at the time of the patient's diagnosis. The imaging examination revealed that the surrounding organs and blood vessels were invaded, which brought great challenges to radical resection. Due to the limited effect of adjuvant therapy, surgical resection is still the only way to cure the disease in patients with retroperitoneal liposarcoma [4, 5]. A persistent problem after the first surgical resection is repeated recurrence of sarcoma. Up to 69-80% of first recurrence cases will have multiple local recurrences[6, 7]. How to treat this type of patient after recurrence? How to deal with blood vessels wrapped by sarcoma during surgery? The medical community has not yet reached the same conclusion. Here we introduce a case of retroperitoneal liposarcoma, which is characterized by repeated recurrences after surgery, and has undergone a total of 6 operations. The postoperative pathology of the patient’s first operation was dedifferentiated liposarcoma, and some areas showed myxofibrosarcoma differentiation. With the recurrence of sarcoma, myxofibrosarcoma dedifferentiated into rhabdomyosarcoma, and malignant fibrous histiocytoma appeared in some areas